LINGUISTIC AND SPIRITUAL SIGNIFICANCE OF UZBEK PROVERBS IN DIFFERENT LANGUAGES - Normuminov Utkir Ishmuradovich (Western European Studies, 2024)
Works related to the art of speech in folk art were created and performed even before the culture of writing was discovered. From oral riddles to short proverbs, from epics to songs, it is spoken orally. Each performer absorbed his own life experience, worldview, relations with compatriots into the sample of his work. Until recently, there was an idea that folklore samples would be polished as samples of oral creativity were passed from generation to generation. In fact, the artistic perfection or weakening of a piece of oral art depends on the skill of the performer. If the work is done by a person who has seen a good teacher and has a talent for artistic creativity, the work will be artistically polished. Otherwise, the beauty of the work may be spoiled.
Keywords: proverb; idiom